Pengaruh Product Knowledge dan Persepsi Nasabah Terhadap Preferensi Menabung di Bank Syariah dengan Disposable Income Sebagai Variabel Moderating - Khasanah Mustika Syahputri; Ahmad Amin Dalimunte (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of the study was to determine the effect ofproduct knowledge and customers perception on the preferences saving in Islamic banks with disposable income as a moderating variable. This type of research uses a quantitative approach. The research population is students of the 2018 Department of islamic banking, State Islamic University of North Sumatra and sampling technique uses purposive sampling with a sample size of 78 students. The analysis model used in this study was linear regression analysis multipel. The results of this study indicate that there is the value of adjusted R square (R2) is 0,431 a direct influence between the product knowledge and customers perception on the preferences saving in Islamic banks. Even so, disposable income cannot moderate product knowledge and customers perception of saving preferences in Islamic banks. It is hoped that further research can use other moderating variables besides the disposable income variable in moderating the relationship between the independent variable and the dependent variable.